The mathematical stability study for the system of the CoO(OH) – overoxidized polypyrrole composite synthesis in the presence of fluor ions - Tkach, V.; de Oliveira, S.C.; Ojani, R.; Yagodynets, P.I.; Páramo-García, U. (Mongolian Journal of Chemistry, 2016)
The potentiostatic synthesis of CoO(OH) – Overoxidized polypyrrole composite in the presence of fluor ions has been investigated mathematically. The corresponding mathematical model was described and analyzed by means of linear stability theory and bifurcation analysis. The steady-state stability requirements, like also oscillatory and monotonic instability conditions are derived. Mongolian Journal of Chemistry 16 (42), 2015, 13-17